Influence Of Modern Chinese Popular Music: The Case Study Of Jay Chou - Lier, Yu Hang (2020)
Among various popular cultures, popular music has embraced world widely by young adults, Malaysian young people are not exempted as well. The influence of music among young adults is widely discussed to look into its uses and gratifications, significance and individual’s interpretation. Modern Chinese popular music has been mostly discussed with its evolution in relation with cultural politics and youth culture. Nonetheless, it has claimed to be lacking in exploration, at least in Malaysia. With a severely lacking representation of modern Chinese popular music in the society, this research is a humble attempt to study the influence of the music, a famous Taiwanese singer, Jay Chou is taken into account as case study. By utilising qualitative approach, the researcher firstly distributed 100 survey questionnaires to obtain first phase of data collection for examining Chou’s popularity among Malaysian Chinese Millennials as well as applying Uses and Gratifications (U&G) approach to understand individual’s needs seek from Chou’s music. As for second phase of data collection, the researcher conducted interview with 5 focus groups with total 30 participants in order to collect personal opinions through discussions. The thematic analysis iii showed the Millennials is actively consuming the modern Chinese popular music whereby having both positive and negative perceptions. By using Jay Chou’s music and his image as case study, both elements are well-recognised which then showed a great extent of communication. With such, it’s tended to be influential tool for the Millennials to receive and derive meaning according to their social context.